Preventive activity of the National Police on juvenile prevention - I. V. Ishchenko (Bulletin of Kharkiv National University of Internal Affairs)
On the basis of the norms of administrative law and current legislation analysis, the preventive activities of the National Police on juvenile prevention were investigated. Consideration of the specified problems within the scope of the article allows to expand the traditional approach to juvenile prevention, not only to connect the issue of prevention of offenses with the prevention of criminal offenses among children, but also to develop measures aimed at preventing administrative offenses committed by this category of persons, as well as the implementation of activities, related to the protection of children’s rights. For this purpose, the role of the National Police units for juvenile prevention in the prevention and counteraction of criminal and administrative offenses through the prism of the main tasks that rely on the latter was clarified and disclosed, and measures aimed at improving preventive and prophylactic work to ensure the rights and legitimate interests of children were also highlighted.